COLLECTIVE ACCOMPANIMENT AS PER THE REFLEXIVITY APPROACH ON-IN-FOR PRACTICE EXPERIENCED BY THREE TYPES OF ACTORS - Houde, Patricia Marie Anne; Guillemette, Suzanne (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
Collective accompaniment, as per the reflexivity approach on-in-for practice, requires the adoption of different postures, whether one is placed in the role of the accompanying or accompanied person. This article presents the lived experiences of an accompaniment process fostering research and training within an individual and collective reflexivity approach. Three types of actors are interrelated: an accompanying research director, an accompanied and accompanying doctoral candidate, and accompanied and accompanying English as a second language teachers. Advocating for an action-research approach using the first-person point of view (“I”), each actor was invited to reflect on their practice from an on-in-for perspective. The discussion presents three dimensions: the role of ethical rules, the art of questioning, and the interdependence between involved actors.